Trend of epidemiological indicators of leprosy in an endemic state of the Amazon region - Maria Eduarda de Macedo Basso; Rosemary Ferreira de Andrade; Rodrigo Luís Ferreira da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To characterize the temporal trend of epidemiological indicators of leprosy in the State of Amapá. Method Time series study, carried out in the Notifiable Diseases Information System. The indicators analyzed were: annual detection rate of new cases, detection rate of new cases in the population from 0 to 14 years old, rate of new cases with grade 2 of disability, proportion of new cases with grade 2 and proportion of new multibacillary cases, between 2005 and 2018. The analysis of the temporal evolution was made by linear regression. Results The detection rate of new cases and the rate of children under 15 years showed a decreasing trend. The rate of new cases with grade 2 of disability and the proportion of cases with grade 2 showed oscillation. The proportions of multibacillary remained constant. Conclusion The epidemiological indicators analyzed suggest active transmission and late diagnosis, signaling a possible hidden endemic disease.